2012
DOI: 10.1111/j.1365-2702.2012.04208.x
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of the lived experiences of adults with intellectual disabilities in a Swedish institutional care setting: a reflective lifeworld approach

Abstract: The results of this study contribute to better insight and deeper knowledge of the lived experiences of adults with intellectual disabilities, enabling the staff and management to further enhance the well-being for residents. In addition, the findings provide feedback to staff, managers and researchers working in the intellectual disabilities field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The results also showed that there are positive benefits to housing and hospitality services for people with intellectual disabilities and autism spectrum disorders, which positively affect their psyche, as confirmed by the families during the interview. These results support what was indicated by study by Hallrup (2014) of daily caring for people with disabilities when they join a housing and hospitality centre. This was indicated by the quantitative results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results also showed that there are positive benefits to housing and hospitality services for people with intellectual disabilities and autism spectrum disorders, which positively affect their psyche, as confirmed by the families during the interview. These results support what was indicated by study by Hallrup (2014) of daily caring for people with disabilities when they join a housing and hospitality centre. This was indicated by the quantitative results.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the study by Hallrup (2014) indicate the need to pay attention to what adults with intellectual disabilities say about their daily lives when they live in a permanent residential care environment. The current study notes the lack of interest in the previous studies in nutritional programmes and physical activity as aspects of housing and hospitality services for people with intellectual disabilities and autism spectrum disorders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Residents were also infantilized and characterized as individuals who are unable to make decisions that are in their best interests. The actions of the habilitation technicians revealed a cultural ambivalence toward residents' desires and interests and their having to live in a restricted life space (Hallrup, 2012).…”
Section: Discussionmentioning
confidence: 99%